The Black-headed Gull Larus ridibundus in Irian Jaya - Bishop, K David; Diamond, Jared M (KUKILA, 1987)
Gulls (Laridae) are a familiar group of birds at temperate and subtropical latitudes in both northern and southern hemispheres. However, they are rarely encountered in the tropics, particularly those of Asia and the Pacific. It is therefore interesting to note a group of 20 Black-headed Gulls Larus ridibundus apparently over-wintering in Sorong harbour at the extreme western tip of Irian Jaya (New Guinea) in January and February 1986.